Multi-physics coupling analysis of an aerostatic spindle - Lihua Lu; Qiang Gao; Wanqun Chen; Guanglin Wang (Advances in Mechanical Engineering, 2017)
The performance of aerostatic spindle is highly affected by the fluid–structure interaction effect between solid structure and air film. In working condition, the viscous heat generated by air film also influences the spindle performance greatly. In this article, the structure deformation induced by pressurized air film and viscous heat is investigated based on a multi-physics coupling model. The simulation results indicate that the structure deformation could lower the load-carrying capacity of air bearing. The reliability of proposed model is verified by experiments.